Effects of Fermi resonance of ν1 and 2ν2 on the Raman scattering of fundamental mode ν2 from liquid carbon disulfide. (January 2017) - Gong, Nan; He, Xin; Zhou, Mi; He, Liqiao; Fan, Limei; Song, Wenzhi; Sun, Chenglin; Li, Zuowei
Graphical abstract: Highlights: The Fermi resonance parameters are calculated and energy is transferred from ν1 to 2ν2 . Mode ν2 is influenced by 2ν2 and its Fermi resonance with ν1 . The first report on the effects of Fermi resonance ν1 and 2ν2 on the fundamental mode ν2 . Abstract: Raman scattering from liquid carbon disulfide has been studied for different concentrations in benzene. Modes ν1 (656 cm −1 ) and 2ν2 (796 cm −1 ) are allowed bands of carbon disulfide, while ν2 (396 cm −1 ) is forbidden by the selection rules. However, a weak band has been observed along with the strong allowed totally symmetrical stretching mode ν1 . The observation is ascribed to the effects of the vibrational anharmonicity of free molecule and intermolecular interaction potential. The ν1 and 2ν2 Fermi resonance can be influenced by the external conditions. The effects of the ν1 and 2ν2 Fermi resonance on the Raman frequency and relative intensity are discussed and the Raman scattering cross section of ν2 is studied for different concentration of carbon disulfide in benzene. The second-order perturbation quantum theory is introduced to explain the results that the Raman scattering of ν2 is influenced by 2ν2 and its Fermi resonance with ν1 .